Kinetics of Hepatitis B Core–Related Antigen and Anti–Hepatitis B Core Antibody and Their Association With Serological Response in Human Immunodeficiency Virus–Hepatitis B Coinfection. (21st January 2020) - Dezanet, Lorenza N C; Maylin, Sarah; Gabassi, Audrey; Rougier, Hayette; Miailhes, Patrick; Lascoux-Combe, Caroline; Chas, Julie; Girard, Pierre-Marie; Delaugerre, Constance; Lacombe, Karine; Boyd, Anders
Abstract: Background: The aim of the current study was to describe the kinetics of quantified hepatitis B core–related antigen (qHBcrAg) and quantified anti–hepatitis B core antibody (qAnti-HBc) during tenofovir (TDF) treatment and assess their ability to predict hepatitis B e antigen (HBeAg) seroclearance in patients coinfected with human immunodeficiency virus (HIV) and hepatitis B virus. Methods: Serum qHBcrAg, qAnti-HBc, and hepatitis B virus DNA were obtained at TDF initiation and every 6–12 months. The on-treatment kinetics of qHBcrAg (ΔqHBcrAg) and qAnti-HBc (ΔqAnti-HBc) were estimated using mixed-effect linear regression. Hazard ratios (HRs) assessing the association between markers and HBeAg seroclearance were calculated using proportional hazards regression, and the sensitivity (Se) and specificity (Sp) of marker levels in predicting HBeAg seroclearance were assessed using time-dependent receiving operating characteristic curves. Results: During a median of 4.6 years, the cumulative incidences of hepatitis B surface antigen and HBeAg seroclearance were 3.2% (n = 5 of 158) and 27.4% (n = 26 of 95), respectively. ΔqHBcrAg was biphasic in HBeAg-positive patients (−0.051 and −0.011 log10 U/mL/mo during ≤18 and >18 months, respectively) and monophasic in HBeAg-negative patients. ΔqAnti-HBc was monophasic regardless of HBeAg status. In HBeAg-positive patients, baseline qHBcrAg and qAnti-HBc levels were associated with HBeAg seroclearance (adjusted HR, 0.48/log10 U/mL [95% confidence interval, .33–.70] and unadjusted HR, 1.49/log10 Paul Ehrlich Institute units/mL [1.08–2.07], respectively). Cutoffs with the highest accuracy in predicting HBeAg seroclearance at 36 months were qHBcrAg <6.5 log10 U/mL at month 24 (Se, 1; Sp, 0.58) and baseline qAnti-HBc ≥4.1 log10 Paul Ehrlich Institute units/mL (Se, 0.42; Sp, 0.81). Conclusions: In coinfected patients undergoing TDF, qHBcrAg/qAnti-HBc could be of use in monitoring HBeAg seroclearance. Abstract : Serum quantification of hepatitis B core–related antigen and anti–hepatitis B core antibodies could be useful in predicting hepatitis B e antigen seroclearance in patients with human immunodeficiency virus–hepatitis B virus coinfection undergoing long-term tenofovir-containing antiretroviral therapy, but they do not perform better than other, currently available markers.